Kenchreai, eastern port of Corinth : results of investigations by the University of Chicago and Indiana University for the American School of Classical Studies at Athens. (Kenchreai. Eastern Port of Corinth, 1976)
Hundreds of richly decorated ivory and bone fragments from furniture and parts from at least three crossed-leg chairs, survived under seawater in an apsidal room at Kenchreai, the Eastern port of ancient Corinth. These excavated remains include fragments of an incised bone panel with a scene of an emperor and attendants, a thiasos, bucolic and hunt scenes, seated philosophers, erotes, and a miniature ivory Corinthian order supporting a bone arcade decorated with erotes. Decorative moldings and large bone rings suggest that most of these belonged to a luxuriously decorated chest. Dating to the fourth century, these objects provide an important addition to our knowledge of the artistic production of late Roman Egypt and the working of ivory, bone, and wood.